2021
DOI: 10.3390/ijerph18052221
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Illegal Toxic Waste Dumping on Children’s Health: A Review and Case Study from Pasir Gudang, Malaysia

Abstract: Poor management of hazardous waste can lead to environmental pollution, injuries, and adverse health risks. Children’s exposure to hazardous waste may cause serious acute and chronic health problems due to their higher vulnerability to the toxic effects of chemicals. This study examines an incident of illegal chemical dumping in Pasir Gudang, Malaysia and its potential health impacts on children. The study introduced a risk assessment of possible health-related effects due to chemical contamination based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Pasir Gudang is an important Malaysian industrial and port city [27]. Along with its rapid development and industry, residents of Pasir Gudang are exposed to multiple of waste caused by human activity [31].…”
Section: Methodsmentioning
confidence: 99%
“…Pasir Gudang is an important Malaysian industrial and port city [27]. Along with its rapid development and industry, residents of Pasir Gudang are exposed to multiple of waste caused by human activity [31].…”
Section: Methodsmentioning
confidence: 99%
“…It has also been found that children who live close to e-waste sites are vulnerable to hazardous organic contaminants. Owing to their vulnerability to environmental toxicants, children have become a significant focus of health effects studies relating to informal e-waste recycling [120][121][122][124][125][126][127][128][129][130]. Children are often exposed through the inhalation of toxic fumes and particulate matter, via skin contact with corrosive chemicals, and by ingesting contaminated food and water [112].…”
Section: Adverse Health Impacts Associated With E-wastementioning
confidence: 99%
“…According to 2017 statistics from the Department of the Environment (DOE), 219 (46%) of 477 rivers surveyed were deemed to be clean, 207 (43%) were mildly contaminated, and 51 (11%) were polluted, a small rise from 2011 levels. Ibrahim et al (2021) noted that in June 2019, approximately 2000 individuals and 111 schools were forced to shut down due to water contamination in the Pasir Gudang river in Sungai Kim. As a result, the report recommended that corporations in Malaysia should embrace Corporate Environmental Responsibility (CER).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%